Validity and Reliability Test of Mathematical Representation Ability Test Instruments in Mathematics Learning - Dika Dani Septiati (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2025)
Mathematical Representation Ability (MRE) is one of the important competencies that need to be mastered by students in learning mathematics. One aspect that can affect students' MRE is the character or thinking patterns possessed by the students. This study aims to evaluate the level of validity and reliability of the test instrument designed to measure the mathematical representation ability of junior high school students in solving algebra problems. The method used is a quantitative descriptive method. Based on the results of the validity test using the Aiken's V formula, the four questions were said to be valid, which indicates that the instrument has very good validity and is suitable for use. Meanwhile, the results of the reliability test showed a correlation coefficient value of 0.795, which indicates a fairly good level of consistency in the reliability category so that it is considered reliable. Thus, this instrument is considered suitable for use by teachers in measuring students' mathematical representation abilities in algebra material.